ANALISIS KINERJA KEUANGAN MENGENAI TINGKAT KESEHATAN BANK DENGAN MENGGUNAKAN METODE CAMELS PADA BANK ACEH DAN BANK SUMUT TAHUN 2008 – 2014 - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2017)
This study to analyze the financial performance of Bank Aceh and Bank SUMUT from 2012 s / d in 2014 in view by using the ratio of CAMELS. The source of the data obtained is secondary data from the Annual Report of Bank Aceh and Bank SUMUT in 2014. Data was collected by study of a literature. Data analysis techniques in this study using descriptive analysis CAMELS ratio in accordance with Bank Indonesia Regulation. The results showed that: The financial performance about the bank’s health rate, PT. Bank Aceh during the period 2012-2014 the bank categorized as